Metagenomic analysis of microflora structure and functional capacity in probiotic Tibetan kefir grains. (January 2022) - Zeng, Xuejun; Wang, Yuwei; Jia, Hang; Wang, Zhouli; Gao, Zhenpeng; Luo, Yane; Sheng, Qinglin; Yuan, Yahong; Yue, Tianli
Graphical abstract: Highlights: A total of 715 species were identified within three TKG communities. Lactobacillus kefiranofaciens is the most dominant species in TKGs (83.3778%). A total of 33 listed probiotics species were identified in TKGs. There are 16 KOs annotated four approaches participate in β-lactam resistant. Abstract: Tibetan kefir grains (TKGs) are distinctive and complex mixtures with protein-lipid-polysaccharide matrices and multiple microorganism species. The objective of this study was to evaluate the microflora composition, probiotic species and functional genes within TKGs. Metagenomic analysis was used to evaluate communities of three TKGs, revealing the presence of 715 species, with Lactobacillus kefiranofaciens as the most dominant species. The relative abundances of acetic acid bacteria and yeast significantly differed among the three TKGs (acetic acid bacteria: p < 0.01; yeast: p < 0.05), and the dominant yeast species also varied across three TKGs. Lactobacillus helveticus was the most abundant listed probiotic species, and its abundance did not significantly differ across three TKGs. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that ko01501 was the most abundant pathway that related to human disease. There are 16 different KOs (KEGG Orthology) in the ko01501 pathway were annotated in TKGs, which helps to resist β-lactam. This study provided a new insight into the microbial community structures and the presence of probiotic species within TKGs and provides a foundation for further targeted studies.